Evaluating antibiotic occurrence, degradation, and environmental risks in poultry litter within Argentina's agricultural hub - Alonso, Lucas L. (2024)
This study explores the relationship between poultry farming's antibiotic administration practices and residual antibiotic levels in the litter before its application onto agricultural soils. Twenty-three antibiotics were performed across 19 Argentinean farms representing diverse antibiotic management practices. Analysis revealed up to 20 antibiotics from eight chemical classes in poultry litter samples, with tylosin, enrofloxacin, and salinomycin being the most relevant drugs. Farms with restricted antibiotic use in feed exhibited lower residual concentrations. A self-heating treatment was tested to reduce litter antibiotic levels. Although a 60 % reduction of antibiotics was found after treatment, prevalent compounds persisted at residual levels. Regulatory measures and comprehensive litter treatments pre-application are crucial to mitigate environmental risks. This is the first study that provides insight on the occurrence of >20 drugs in real poultry production scenarios from Latin America and demonstrates how relatively simple treatments can be readily applied to decrease the associated environmental risks.